Volunteerism and international sport organisations: XVII. Mediterranean Games - Hulya Unlu; Melike Esentas; Pinar Guzel; Selhan Ozbey (Türk Spor ve Egzersiz Dergisi)
After the recent candidacy process and while the Olympic Games are going on to be a dream, very important and large-scale organizations are continuing to be done in our Country. The head of them is XVII. Mediterranean Games which can not be placed in Greece because of economical reasons. One of the most important activities as such large and the successful execution of the multi-level voluntary organization of sporting events lead voluntary organization. The aim of this study; is to determinate the demographics and causes of participation of volunteers who are employed in the Games of which Mersin is the host, and to determinate the volunteers at the individual and activity level during the Games. In this study, the method of qualitative research approach is applied on 29 employed volunteers in Games. At the end of the interviews face to face with volunteers; the assessments on individual and activity level during the organisation and demographic characteristics and causes of participation are revealed.